Pre-service and in-service EFL teachers’ levels of reflection - Tagle Ochoa, Tania; Paola Alarcón Hernández, Claudio Díaz Larenas; Quintana Lara, Marcela; Ramos Leiva, Lucía; Etchegaray Pezo, Paulo (Opción, 1970)
The objective of this study is to identify the levels of reflection achieved by Chilean pre-service and in-service teachers of English based on their classroom performance. This research was qualitative and employed a case study design. The participants were 121 pre-service teachers and 54 novice in-service teachers from Chile. In order to collect data, a reflection form was completed by them. The results indicate that the participants only show a descriptive level of reflection, which is the most basic. It is suggested that English language teacher education programs promote reflection, at higher levels, in undergraduate courses of didactics and practicum.